Biota Dose Assessment of Small Rodents Sampled Near Breccia Pipe Uranium Mines in the Grand Canyon Watershed. Issue 1 (July 2019) - Minter, Kelsey M.; Jannik, G. Timothy; Hinck, Jo Ellen; Cleveland, Danielle; Kubilius, Walter P.; Kuhne, Wendy W.
Abstract : Abstract: The biotic exposure and uptake of radionuclides and potential health effects due to breccia pipe uranium mining in the Grand Canyon watershed are largely unknown. This paper describes the use of the RESRAD-BIOTA dose model to assess exposure of small rodents ( n = 11) sampled at three uranium mine sites in different stages of ore production (active and postproduction). Rodent tissue and soil concentrations of naturally occurring uranium ( 234 U, 235 U, and 238 U), thorium ( 228 Th, 230 Th, and 232 Th), and radium ( 226 Ra) radioisotopes were used in the dose model. The dose assessment results indicated that the potential internal, external, and total doses to rodents were below the US Department of Energy's biota dose standard of 1 mGy d −1 . As expected, tissue concentrations of 238 U, 234 U, and 230 Th were in approximate equilibrium; however, 226 Ra results in tissue were 1.25 to 5.75 times greater than 238 U, 234 U, and 230 Th tissue results for 10 out of 11 samples. Soil at the three sites also displayed 226 Ra enrichment, so it is likely that the 226 Ra enrichment in the rodents was from soil via typical activities (i.e., burrowing, incidental ingestion, bathing, etc.) or by dietary uptake of translocated 226 Ra. The results suggest that 226 Ra is more mobile in this environment and bioaccumulates in these rodent species (e.g., in bones via the bloodstream). Internal dose accounting suggests that 226 Ra is the radionuclide of most concern for rodent exposure and health.